2023
DOI: 10.3390/ani13010184
|View full text |Cite
|
Sign up to set email alerts
|

Loci Associated with Negative Heterosis for Viability and Meat Productivity in Interspecific Sheep Hybrids

Abstract: Negative heterosis can occur on different economically important traits, but the exact biological mechanisms of this phenomenon are still unknown. The present study focuses on determining the genetic factors associated with negative heterosis in interspecific hybrids between domestic sheep (Ovis aries) and argali (Ovis ammon). One locus (rs417431015) associated with viability and two loci (rs413302370, rs402808951) associated with meat productivity were identified. One gene (ARAP2) was prioritized for viabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Our study also identified some genes related to meat production. Zlobin et al (2023) identified protocadherin 15 (PCDH15), a gene associated with meat productivity, between domesticated sheep (Ovis aries) and pan sheep (Ovis ammon), which is consistent with a super-dominant model of inheritance. Kizilaslan et al (2022) studied the genetic structure of growth-and linear-type traits in Akkaraman sheep and proposed 22 genes, among which transducin-like enhancer of split-4 (TLE4) and transcription factor AP-2 β (TFAP2B) were same as the genes found in this study (Kizilaslan et al, 2022).…”
Section: Fat-and Growth-related Genessupporting
confidence: 58%
“…Our study also identified some genes related to meat production. Zlobin et al (2023) identified protocadherin 15 (PCDH15), a gene associated with meat productivity, between domesticated sheep (Ovis aries) and pan sheep (Ovis ammon), which is consistent with a super-dominant model of inheritance. Kizilaslan et al (2022) studied the genetic structure of growth-and linear-type traits in Akkaraman sheep and proposed 22 genes, among which transducin-like enhancer of split-4 (TLE4) and transcription factor AP-2 β (TFAP2B) were same as the genes found in this study (Kizilaslan et al, 2022).…”
Section: Fat-and Growth-related Genessupporting
confidence: 58%
“…Negative dominant effects have been reported in other species. Zlobin et al (2023) reported the loci associated with negative heterosis for viability and meat productivity in interspecific hybrids between domestic sheep and argali. Clasen et al (2017) observed negative heterosis effects for the period from first calving until culling in Danish Jersey × Danish Holstein and Danish Jersey × Danish Red crosses.…”
Section: Resultsmentioning
confidence: 99%
“…Occasionally, we also included specific animal (e.g., sheep, goats or cattle) as an additional keyword to refine the results. We then summarized all the previously reported genes in terms of function and animal in Additional file 2 : Table S30 [ 28 , 30 , 31 , 35 38 , 41 , 43 47 , 103 , 114 , 247 306 ]. To eliminate potential bias in the results of literature review, we did not use the literature including the same sheep/goat individuals as the present study for gene comparison.…”
Section: Methodsmentioning
confidence: 99%